2018
DOI: 10.7150/thno.28219
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytes fuel gastric cancer omental metastasis via PITPNC1-mediated fatty acid metabolic reprogramming

Abstract: Omental metastasis occurs frequently in gastric cancer (GC) and is considered one of the major causes of gastric cancer-related mortality. Recent research indicated that omental adipocytes might mediate this metastatic predilection. Phosphatidylinositol transfer protein, cytoplasmic 1 (PITPNC1) was identified to have a crucial role in metastasis. However, whether PITPNC1 participates in the interaction between adipocytes and GC omental metastasis is unclear.Methods: We profiled and analyzed the expression of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 40 publications
(47 reference statements)
1
73
0
Order By: Relevance
“…3a), supporting our hypothesis that ATOH8 high CTCs is prone to survival in the circulation. On the other hand, our previous studies have found that metabolic reprogramming is a key factor mediating the anoikis resistance of tumour cells [24]. Further, to explore the association between metabolism and the ATOH8 mediated CTC survival, ssGSEA analyses were performed, and the data revealed that only glycolysis, a vital metabolic pathway in tumour cells, was significantly different between ATOH8 high and ATOH8 low , rather than fatty acid metabolism, oxidative phosphorylation and amino acid metabolism ( Fig.…”
Section: Atoh8 Promotes Crc M-ctcs Survival Via Hk2-mediated Glycolysismentioning
confidence: 91%
See 1 more Smart Citation
“…3a), supporting our hypothesis that ATOH8 high CTCs is prone to survival in the circulation. On the other hand, our previous studies have found that metabolic reprogramming is a key factor mediating the anoikis resistance of tumour cells [24]. Further, to explore the association between metabolism and the ATOH8 mediated CTC survival, ssGSEA analyses were performed, and the data revealed that only glycolysis, a vital metabolic pathway in tumour cells, was significantly different between ATOH8 high and ATOH8 low , rather than fatty acid metabolism, oxidative phosphorylation and amino acid metabolism ( Fig.…”
Section: Atoh8 Promotes Crc M-ctcs Survival Via Hk2-mediated Glycolysismentioning
confidence: 91%
“…BALB/c female nude mice 4-5 weeks of age were purchased from the Experimental Animal Centre, Southern Medical University (Guangzhou, China) and maintained in specific pathogen-free conditions. Subcutaneous tumour and metastatic tumour mouse models were generated as described previously [24]. Details are available in the supplementary materials (Additional file 1: Supplementary methods and materials).…”
Section: Micementioning
confidence: 99%
“…It has been reported that facilitation of FAO contributed to the resistance of cancer cells to drugs and aggravated tumorigenesis [25][26][27][28][29][30] . Previous works have associated FAO to GC by demonstrating that FAO induced the metastasis and that MSC co-culture aggravated FAO and improved stemness and chemoresistance in GC 31,32 . Therefore, it was reasonable to deduce that HCP5/miR-3619-5p could regulate FAO in GC.…”
Section: Discussionmentioning
confidence: 99%
“…uncovered to play a role in chemo-resistance, stemness, and tumorigenesis in cancer cells [27][28][29][30] . Also, it has been proved that the facilitated FAO can induce metastasis, confer chemo-resistance and improve stemness of GC cells 31,32 . Thus, we hypothesized that MSC-activated HCP5/miR-3619-5p regulated FAO in GC cells.…”
Section: Msc-activated Hcp5/mir-3619-5p Axis Regulated Fao In Gcmentioning
confidence: 99%
See 1 more Smart Citation